STUDY OF SYMBIOSIS FORMATION CONTROL IN PEA MUTANTS BY THE VEGETATIVE GRAFT METHOD - E. Yu. Vlasova; K. K. Sidorova; M. N. Glyanenko; T. M. Mishchenko (Вавиловский журнал генетики и селекции)
Eight symbiotic mutants of pea (Pisum sativum L.) induced by chemical mutagenesis have been studied by the vegetative graft method in a «stem/root» manner. It has been found that symbiotic traits are controlled by the root in nonnodulating mutants K20a and K1005m, mutants with ineffective nodules K287 and K1a and supernodulating mutants K10a and K12a. In contrast, in supernodulating mutants K301 and K22a these traits are controlled by the stem. It is concluded that different mechanisms control supernodulation in supernodulating mutants K10a and K12a, on the one hand, and K301 and K22a, on the other hand.